How does the UK public think and feel about people with visual impairment: a review of existing evidence - Heinze, Nikki; Jones, Lee; Bertiz, Firuzé; Saunders, Emma; Gomes, Renata S. M. (Frontiers in Psychology, 2024)
Despite legislation to protect people with visual impairment (V.I.) from discrimination in the United Kingdom (UK), the latter continue to experience overt and covert negative behaviours. Perceived discrimination has been associated with an adverse impact on identity, health and well-being, while negative attitudes have been identified as the biggest barrier to participation in everyday life. This article provides a narrative review of existing evidence of how the UK public treats (behaviours), thinks (perceptions) and feels (attitudes) about people with V.I. Despite limitations, the findings suggest that there is a gap between the behaviours reported by people with V.I. and the attitudes expressed by members of the UK public. Social psychological theories are used to explore possible reasons for this gap, and ways in which it may be addressed. As such, the article provides an example of how social psychological theories can be used to address problems in an applied context.